Anhydrous magnesium sulfate mediated solvent-free synthesis of dihydropyrimidin-2(1H)-ones at ambient temperature - Pore, D. M.; Desai, Uday V.; Thopate, T. S.; Wadgaonkar, P. P. (Australian Journal of Chemistry, 2007)
An anhydrous magnesium sulfate mediated solvent-free protocol is described for the synthesis of dihydropyrimidinones (Biginelli compounds) at ambient temperature.